Implementasi Strategi Vrio (Valuable, Rare, Inimitable, Organization) Pada Pengrajin Tas Anyaman Kampung Rejoso - Farika Nikmah; Halid Hasan; Erlangga Andi Sukma; Becik Gati Anjari; Rizka Rahmawati (LPPM STIKOM Tunas Bangsa, 2022)
Pengabdian kepada Masyarakat (PkM) activity is a form of concern for collaboration and synergy between academics and the community, represented by small business entrepreneurs. Bu Siti Woven Bag Craft is a small business that has the opportunity to develop and provide opportunities for local residents to get jobs. PkM activities are an effort to strengthen the internal resources of small businesses by implementing the VRIO strategy. Prioritizing the concept of the valuable, rare, inimitable organization, PkM activities try to provide solutions by strengthening owner perceptions, strengthening products and strengthening organizations. Activities through counseling, discussion and mentoring by first identifying the problems faced by partners. The results of PkM activities have an impact on increasing the owner's confidence in running his business, increasing knowledge about how to make unique products, as well as considering efficiency in the production process to get a higher profit.